CARTOGRAPHIE DU RISQUE D’INONDATION PAR UNE APPROCHE COUPLÉE DE LA TÉLÉDÉTECTION ET DES SYSTЀMES D’INFORMATIONS GÉOGRAPHIQUES (SIG) DANS LE DÉPARTEMENT DE SINFRA (CENTRE-OUEST DE LA COTE D ’IVOIRE) - N’guessan Bi, Vami Herman; Saley, Bachir; Wade, Soulèye; Eric Valere, Djagoua; Kouame, Fernand; Affian, Kouadio (European Scientific Journal, ESJ, 2014)
The objective of this study is to evaluate and spatialize the risk of flooding in the department Sinfra located in west-central Côte d’Ivoire, with a view to prevention, through the combined use of remote sensing and Geographic Information Systems (GIS). In this study the risk of flooding has been addressed in two main areas such as risk overflowing rivers and the risk associated with the rise of groundwater. This analysis also identified areas of risk of flooding for priority action. Thus the risk of flooding due to overflowing of rivers is present in the Western of the department of Sinfra, in a proportion of 17% and is less higher than the risk associated with the rise of groundwater which represents approximately 38% of the department and concerns mainly areas situated in the center and East of the department.